Synthesis of Antihemophilic Factor Antigen by Cultured Human Endothelial Cells - Jaffe, Eric A. (1973)
Antihemophilic factor (AHF, Factor VIII) antigen has been demonstrated in cultured human endothelial cells by immunofluorescence studies using monospecific rabbit antibody to human AHF. Control studies with cultured human smooth muscle cells and human fibroblasts were negative. By radioimmunoassay it was demonstrated that cultured human endothelial cells contain AHF antigen which is released into the culture medium. Cultured smooth muscle cells and fibroblasts did not have this property. Cultured endothelial cells incorporated radioactive amino acids into high molecular weight, AHF antigen-rich protein fractions prepared from the culture media, 7% of the radioactive amino acid counts incorporated into this material were precipitated by globulin prepared from rabbit anti-AHF whereas normal rabbit globulin precipitated only 1.5% of the counts. Although cultured endothelial cells actively synthesize AHF antigen, AHF procoagulant activity was not detected in the culture medium. Studies seeking a basis for the lack of procoagulant activity have not clarified this deficiency, but they have established that exogenous AHF procoagulant activity is not inactivated by the tissue culture system.